Physical Examination Results and Medical Supporting Evidence Affect the Accuracy of Pneumonia Diagnosis Codes in Hospitals - Heltiani, Nofri; Arifin, Ismail; Khairunnisyah (Sekolah Tinggi Ilmu Kesehatan Sapta Bakti, 2025)
The Ministry of Health of the Republic of Indonesia, Decree No. HK.02.02/Menkes/514/2015, states that pneumonia is one of the diseases frequently leading to medical disputes, resulting in losses for hospitals. Based on an initial survey of 10 pneumonia medical records, five files contained missing supporting examination results (chest x-ray), two files contained incomplete physical examinations, and three files contained complete records (chest x-ray, physical examination), leading to doubts about the pneumonia diagnosis codes written in the medical records. This study aimed to determine the accuracy of pneumonia diagnosis codes by examining the results of physical examinations and medical support at Hospital X in 2024. This study was a quantitative descriptive study with a population and sample of 96 medical records of pneumonia cases. The data used in this study were primary and secondary data, using interview guidelines and observation sheets. The data were then processed and analyzed univariately using frequency distribution. The results of the study revealed that the completeness of the physical examination results and medical support was 38 (39%), the accuracy of the physical examination results and medical support was 35 (36%), and the accuracy of the pneumonia diagnosis code was 47 (49%). It is hoped that the Head of Medical Records will conduct a medical record audit through qualitative analysis to minimize the occurrence of medical disputes.